Synthesis of Turpentine Oil Based Carbon Nanospheres by Nebulized Spray Pyrolysis Method - Arie, Arenst Andreas; Konstantia, Inez Devina; Susanti, Ratna Frida; Devianto, Hary; Halim, Martin; Lee, Joong Kee (AMER SCIENTIFIC PUBLISHERS, 2016)
In this study, production of carbon nano-spheres (CNSs) was conducted by the decomposition of botanical hydrocarbons, known as turpentine oil (C10H16) using activated carbon as a substrate. The oil decomposition was carried out by nebulized spray pyrolysis method operated at temperature of 700 degrees C for 30 minutes of deposition time by varying the concentration of ferrocene catalyst dissolved in the oil i.e., 0.015, 0.02, and 0.025 g/ml. The carbon products were characterized by Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Raman spectroscopy and X-ray Diffraction (XRD), respectively. The SEM observations showed that the as grown carbon materials were formed as agglomerated CNSs. The TEM results showed that the highest concentration of ferrocene favors the formation of carbon nanotubes (CNTs). Raman analysis revealed that the intensity ratio between disorder and graphite like structure (I-D/I-G) was in the range 0.87-0.93. On the other hand, XRD results showed that the as grown product contains no metal catalyst contaminants.